How green marketing mix strategies affects the firm's performance: a Malaysian perspective. (8th April 2019) - Goh, Wan-Har; Goh, Yen-Nee; Ariffin, Shaizatulaqma Kamalul; Salamzadeh, Yashar
Green approaches are a 'must' in the current business environment given the importance of environmental issues in different aspects of business activities in different businesses such as electrical and electronics manufacturing firms. Green marketing strategies are one of the main green approaches in manufacturing industry influencing environmental outcomes and firm performance in different levels. This study aims to investigate the effects of green marketing mix program on firm performance. A survey is conducted in E&E manufacturing firms in Malaysia under the Federation of Malaysian Manufacturers (FMM) 2014. We gathered 121 questionnaires from marketing managers or business development managers in this industry. We studied the impacts of green product, green price, green place, and green promotion, on firm performance using a stakeholder-theory-based conceptual model. The research findings show that green product, green price, and green promotion significantly influence firm performance in E&E manufacturing firms in Malaysia.